2015
DOI: 10.7575/aiac.alls.v.6n.4p.103
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Effects of Comprehensible Input, Output and Corrective Feedback on the Receptive Acquisition of L2 Vocabulary Items

Abstract: In the present study, the comparative effects of comprehensible input, output and corrective feedback on the receptive acquisition of L2 vocabulary items were investigated. Two groups of beginning EFL learners participated in the study. The control group received comprehensible input only, while the experimental group received input and was required to produce written output. They also received corrective feedback on their lexical errors if any. This could result in the production of modified output. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The results revealed that receiving comprehensible input, although beneficial, cannot account for language acquisition. Another study conducted by Nowbakht and Shahnazari (2015) focused on the comparative effects of comprehensible input, output, and corrective feedback on the vocabulary development of EFL learners. The experiment group, which received input and was required to produce written output as well as receiving corrective feedback, outperformed the control group, which received comprehensible input only.…”
Section: Is 'Only' Comprehensible Input Sufficient For Language 'Acquisition'?mentioning
confidence: 99%
“…The results revealed that receiving comprehensible input, although beneficial, cannot account for language acquisition. Another study conducted by Nowbakht and Shahnazari (2015) focused on the comparative effects of comprehensible input, output, and corrective feedback on the vocabulary development of EFL learners. The experiment group, which received input and was required to produce written output as well as receiving corrective feedback, outperformed the control group, which received comprehensible input only.…”
Section: Is 'Only' Comprehensible Input Sufficient For Language 'Acquisition'?mentioning
confidence: 99%